1989
DOI: 10.1136/hrt.62.6.445
|View full text |Cite
|
Sign up to set email alerts
|

Physiological hypertrophy of the heart and atrial natriuretic peptide during rest and exercise.

Abstract: Atrial natriuretic peptide is a circulating hormone secreted by the atrial myocytes of the heart. It is released in response to increased atrial pressure,' which is generally equal to increased stretch and dilatation of the atrial wall. Plasma atrial natriuretic peptide rose during exercise.2The term "athelete's heart" was introduced byHenschen in 1899.' In this condition all the chambers of the heart are dilated and there is hypertrophy of the myocardium due to physical training.4"The purpose of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Dual chamber pacing in complete heart block restores atrial natriuretic peptide concentrations to normal in most patients and this has been offered as evidence of the physiological nature of this mode.22 By contrast, VVIR pacing did not restore normal concentrations. It has previously been shown that atrial natriuretic peptide concentrations rise on exercise23 24 and during ventriculoatrial pacing.25 By providing higher ventricular rates on exercise, VVIR pacing increases the frequency of asynchronous atrial contraction, which may result in an augmented rise in atrial natriuretic peptide on exercise even in the absence ofintact ventriculoatrial conduction. We did find a trend towards higher concentrations on exercise in the VVIR mode than in the DDD mode (exact p value = 005), but there was no difference between modes in either the absolute or percentage change on exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dual chamber pacing in complete heart block restores atrial natriuretic peptide concentrations to normal in most patients and this has been offered as evidence of the physiological nature of this mode.22 By contrast, VVIR pacing did not restore normal concentrations. It has previously been shown that atrial natriuretic peptide concentrations rise on exercise23 24 and during ventriculoatrial pacing.25 By providing higher ventricular rates on exercise, VVIR pacing increases the frequency of asynchronous atrial contraction, which may result in an augmented rise in atrial natriuretic peptide on exercise even in the absence ofintact ventriculoatrial conduction. We did find a trend towards higher concentrations on exercise in the VVIR mode than in the DDD mode (exact p value = 005), but there was no difference between modes in either the absolute or percentage change on exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Only one patient requested early crossover (5 4) 58-4 (6 0) Oxygen consumption at anaerobic threshold (ml/min/kg) 16-7 ( 0 9) 16-8 (0-9) Maximal carbon dioxide production (ml/min/kg) 24 from VVIR back to DDD for symptoms consistent with pacemaker syndrome. This was the only patient with evidence of intact ventriculoatrial (VA) conduction.…”
Section: Symptomsmentioning
confidence: 99%
“…Similarly, resting levels of A-type NPs are driven by LA size in the setting of cardiovascular pathology (7,10). In contrast, resting levels of B-and A-type NPs are similar among endurance athletes with EICR and healthy normally active controls (1,24,31). This suggests that physiologic hypertrophy has different biochemical characteristics than pathologic hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the magnitude of MECPET-induced NP release was significantly lower following ET (Table 4). Specifically, MR-proANP increase from rest to peak exercise was reduced from 115 [95,127]% to 78 [59,87]%, (P ϭ 0.04), and NT-proBNP increase from rest to peak exercise was reduced from 46 [31,70]% to 27 [25,37]%, (P ϭ 0.02) (Figs. 2 and 3).…”
Section: Study Group Demographics and Historical Parametersmentioning
confidence: 99%
“…In healthy subjects, trained and untrained individuals did not show differences in the concentration of plasma ANP at rest, or during any workload. The size of the chambers on the left side of the heart or left ventricular hypertrophy does not seem to influence the concentration of plasma ANP at rest or during exercise (Svanegaard et al. , 1989).…”
Section: Discussionmentioning
confidence: 99%